La rétroactivité d'une loi à caractère criminel - Manganas, Antoine (Les Cahiers de droit, 1980)
The present study deals with two particular aspects of the problem of retrospective operation of criminal statutes. The principle of the retrospective operation of a procedural statute, as will be seen first, bears some exceptions. S. 36 of the Interpretation Act in particular prescribes that the retrospective operation of procedural enactments takes place only to the extent that the new rules of procedure may be adapted to proceedings taken before the new rules came into effect (R. v. Mustapha Ali). Yet, as will be seen subsequently, it is often very difficult to distinguish between an enactment of substantive nature and one of procedural nature in order to give a retrospective operation to the latter only. This difficulty arose particularity after the modifications of the Criminal Code concerning the offence of driving a motor vehicle with more than a specified proportion of alcohol in the blood (R. v. Johnston). After a brief discussion of those two cases, the author suggests that it is the duty of the legislator to indicate in clear terms what the retrospective operation of a new statute will be, in order to avoid many problems of interpretation.